Do Brand Attachment and Brand Love Truly Mediate the Influence of Consumer Satisfaction on Brand Loyalty Towards Wardah Cosmetic Products? - Vita Yuniar; Soepatini Soepatini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence consumer satisfaction towards brand loyalty mediated by brand attachment and brand love for Wardah cosmetic products. This study uses a quantitative method with the SEM-PLS analysis approach, involving 160 respondents who are Wardah product users. Data were collected through an online questionnaire. The results of the study show that consumer satisfaction has a significant effect on brand attachment. Consumer satisfaction also has a significant effect on brand love. Consumer satisfaction has a significant direct effect on brand loyalty. Then, brand attachment has a significant direct effect on brand loyalty. Brand love also has a significant effect on brand loyalty. In addition, brand attachment is proven to be a significant mediator between brand satisfaction and brand loyalty. Then, brand love is also proven to be a significant mediator between consumer satisfaction and brand loyalty.